Long-Term Dietary Restriction Leads to Development of Alternative Fighting Strategies - Legros, Jeanne; Tang, Grace; Gautrais, Jacques; Fernandez, Maria Paz; Trannoy, Séverine (Frontiers in Behavioral Neuroscience, 2021)
In competition for food, mates and territory, most animal species display aggressive behavior through visual threats and/or physical attacks. Such naturally-complex social behaviors have been shaped by evolution. Environmental pressure, such as the one imposed by dietary regimes, forces animals to adapt to specific conditions and ultimately to develop alternative behavioral strategies. The quality of the food resource during contests influence animals' aggression levels. However, little is known regarding the effects of a long-term dietary restriction-based environmental pressure on the development of alternative fighting strategies. To address this, we employed two lines of the wild-type Drosophila melanogaster Canton-S (CS) which originated from the same population but raised under two distinct diets for years. One diet contained both proteins and sugar, while the second one was sugar-free. We set up male-male aggression assays using both CS lines and found differences in aggression levels and the fighting strategies employed to establish dominance relationships. CS males raised on a sugar-containing diet started fights with a physical attack and employed a high number of lunges for establishing dominance but displayed few wing threats throughout the fight. In contrast, the sugar-free-raised males favored wing threats as an initial aggressive demonstration and used fewer lunges to establish dominance, but displayed a higher number of wing threats. This study demonstrates that fruit flies that have been raised under different dietary conditions have adapted their patterns of aggressive behavior and developed distinct fighting strategies: one favoring physical attacks, while the other one favoring visual threats.